Sick leave and medical leave in the United States: A categorization and recent trends - Stefan Pichler; Nicolas R. Ziebarth (Institute of Labor Economics (IZA), 2024)
This article reviews the current debate about sick pay mandates and medical leave in the United States. The United States is one of three industrialized countries that do not guarantee access to paid sick leave for all employees. We first provide a categorization of the different paid leave concepts such as sick leave, medical leave, or temporary disability insurance, both in a domestic and an international context. Then we use data from the National Compensation Survey to sketch employee coverage rates by type of job. We also document changes since 2010, focusing on paid sick leave. Although gaps in access have decreased over the past decade, we still find large inequalities in access to paid sick leave: While overall coverage increased to 78% in 2023 from 64% in 2015, about half of all parttime employees, employees in the bottom quarter of the wage distribution, and employees in the accommodation and food industry still have no access to paid sick leave benefits. In the last part, we discuss implications of the lack of access to paid sick and medical leave benefits. Moreover, building on international research findings and experiences, we discuss what a possible integration, coordination, and expansion of the co-existing programs could look like.
Keywords: I12; I13; I18; J22; J28; J32; 330; sick pay mandates; sick leave; medical leave; paid leave; inequality; employer mandates; fringe benefits; moral hazard; unintended consequences; labor costs; National Compensation Survey (NCS)